Off-label use of clomiphene citrate to treat anabolic androgenic steroid induced hypogonadism upon cessation among men (CloTASH) – A pilot study protocol - Ingrid Amalia Havnes; Hans Christian Bordado Henriksen; Per Wiik Johansen; Astrid Bjørnebekk; Sudan Prasad Neupane; Jonny Hisdal; Ingebjørg Seljeflot; Christine Wisløff; Marie Lindvik Jørstad; Jim McVeigh; Anders Palmstrøm Jørgensen (MethodsX, 2024)
Background: Non-prescribed anabolic androgenic steroid (AAS) use is associated with AAS-induced hypogonadism (ASIH), and metabolic, cardiovascular, and mental health risks. Symptoms of ASIH (fatigue, depression, anxiety, sexual dysfunction) are hard to endure following cessation, but there is no consensus on whether endocrine treatment should be used to treat ASIH. This proof-of-concept study aims to explore safety of off-label clomiphene citrate therapy, whether the treatment will reduce the symptoms of androgen deficiency, and to study changes in health risks after cessation. Methods: In this open-labeled non-randomized off-label hormone intervention pilot study, we shall include males with AAS dependence intending to cease use. The 16-week intervention included clomiphene citrate, transdermal testosterone gel for the first four weeks and optional human chorionic gonadotropin (hCG) from week 4 if low treatment response. Measures of physical and mental health will be examined from ongoing AAS use, during the intervention, and at 6- and 12 months post cessation. Change in self-reported symptoms of hypogonadism and other withdrawal symptoms will be compared with data from a group of men who ended AAS use temporarily without the medical intervention. The study may provide valuable clinical insights and may be used to inform the design of future intervention studies.